2018
DOI: 10.3390/rs10020225
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Neolithic Burial Mounds from LiDAR-Derived Elevation Data Using a Multi-Scale Approach and Machine Learning Techniques

Abstract: Airborne LiDAR technology is widely used in archaeology and over the past decade has emerged as an accurate tool to describe anthropomorphic landforms. Archaeological features are traditionally emphasised on a LiDAR-derived Digital Terrain Model (DTM) using multiple Visualisation Techniques (VTs), and occasionally aided by automated feature detection or classification techniques. Such an approach offers limited results when applied to heterogeneous structures (different sizes, morphologies), which is often the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
95
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 28 publications
0
95
0
4
Order By: Relevance
“…Template matching has been used to map burials from optical satellite data (Trier et al, ), and to identify a range of objects including pitfall traps, charcoal burning platforms, and grave mounds in a digital terrain model (DTM) derived from ALS (Schneider, Takla, Nicolay, Raab, & Raab, ; Trier & Pilø, ; Trier & Pilø, ; Trier, Pilø, & Johansen, ; Trier, Zortea, & Tonning, ). Also based on a DTM is an automatic pit filling method based on an inverted DTM to locate mound structures (Freeland et al, ); a combination of curvature estimates, topographic position index, and circular Hough transform to detect prehistoric barrows (Cerrillo‐Cuena, ); a combination of segmentation and template matching to detect grazing structures (Toumazet et al, ); and local contrast in the DTM at three different scales and a random forest classifier to detect burial mounds (Guyot et al, ). A study to detect rectangular enclosures in panchromatic satellite images (Zingman et al, ) concluded that bespoke methods in some cases perform better than using a pre‐trained deep CNN, but at the cost of much longer development time.…”
Section: Introductionmentioning
confidence: 99%
“…Template matching has been used to map burials from optical satellite data (Trier et al, ), and to identify a range of objects including pitfall traps, charcoal burning platforms, and grave mounds in a digital terrain model (DTM) derived from ALS (Schneider, Takla, Nicolay, Raab, & Raab, ; Trier & Pilø, ; Trier & Pilø, ; Trier, Pilø, & Johansen, ; Trier, Zortea, & Tonning, ). Also based on a DTM is an automatic pit filling method based on an inverted DTM to locate mound structures (Freeland et al, ); a combination of curvature estimates, topographic position index, and circular Hough transform to detect prehistoric barrows (Cerrillo‐Cuena, ); a combination of segmentation and template matching to detect grazing structures (Toumazet et al, ); and local contrast in the DTM at three different scales and a random forest classifier to detect burial mounds (Guyot et al, ). A study to detect rectangular enclosures in panchromatic satellite images (Zingman et al, ) concluded that bespoke methods in some cases perform better than using a pre‐trained deep CNN, but at the cost of much longer development time.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological variables used for classification include: Circularity (Davis et al, ; Freeland et al, ; Witharana et al, ) Rectangularity (Zingman et al, ) Area (Davis et al, ; Magnini et al, ; Witharana et al, ) Length and width (Magnini et al, ; Toumazet, Vautier, Roussel, & Dousteyssier, ) Size (Cerrillo‐Cuenca, ; Davis et al, ; Zingman et al, ) Curvature (Cerrillo‐Cuenca, ) Edge detection (Traviglia & Torsello, ; Witharana et al, ; Zingman et al, ) Elevation (Davis et al, ; Guyot et al, ) …”
Section: Obia and Machine Learning In Archaeologymentioning
confidence: 99%
“…Implementing OBIA with a greater number of variables (including multiple scales of analysis) and using higher‐resolution datasets improves accuracy for archaeological prospection (e.g. Guyot, Hubert‐Moy, & Lorho, ; Sevara & Pregesbauer, , 142; Witharana, Ouimet, & Johnson, ).…”
Section: Obia and Machine Learning In Archaeologymentioning
confidence: 99%
See 2 more Smart Citations